Cohort profile: a nationwide population-based retrospective assessment of oesophageal cancer in the Finnish National Esophago-Gastric Cancer Cohort (FINEGO). Issue 10 (14th October 2020) - Söderström, Henna K; Räsänen, Jari; Saarnio, Juha; Toikkanen, Vesa; Tyrväinen, Tuula; Rantanen, Tuomo; Valtola, Antti; Ohtonen, Pasi; Pääaho, Minna; Kokkola, Arto; Kallio, Raija; Karttunen, Tuomo J; et al.
Abstract : Purpose: The Finnish National Esophago-Gastric Cancer Cohort (FINEGO) was established to combine the available registry data with detailed patient information to form a comprehensive, retrospective, population-based research platform of surgically treated oesophageal and gastric cancer in Finland. This cohort profile describes the 2045 surgically treated patients with oesophageal cancer included in the FINEGO cohort. Participants: Registry data were collected from the National Cancer, Patient, Education and Death Registries from 1 January 1987 to 31 December 2016. All patients over 18 years of age, who had either curative surgery, palliative surgery or salvage surgery for primary cancer in the oesophagus are included in this study. Findings to date: 2045 patients had surgery for oesophageal cancer in the selected time period. 67.2% were man, and the majority had only minor comorbidities. The proportions of adenocarcinomas and squamous cell carcinomas were 43.1% and 44.4%, respectively, and 12.5% had other or missing histology. Only about 23% of patients received neoadjuvant therapy. Oesophagectomy was the treatment of choice and most patients were treated at low-volume centres, but median annual hospital volume increased over time. Median overall survival was 23 months, 5-year survival for all patients in the cohort was 32.9% and cancer-specific survival was 36.5%. Future plans: Even though Finland only has a population of 5.5 million, surgery for oesophageal carcinoma has not been centralised and therefore previously reported results have mostly been small, single-centre cohorts. Because of FINEGO, we now have a population-based, unselected cohort of surgically treated patients, enabling research on national trends over time regarding oesophageal cancer, including patient characteristics, tumour histology, stage and neoadjuvant treatment, surgical techniques, hospital volumes and patient mortality. Data collection is ongoing, and the cohort will be expanded to include more detailed data from patient records and national biobanks.